Konsep Dakwah Politik Mohammad Natsir di Indonesia - Sri Harda Yanti; M. Fatchurrohman; Herri Gunawan (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This research is included in library research with a socio-historical approach. This research is included a qualitative research. This research belongs to the type of historical study through the study of documents or texts. This study discusses the concept of Mohammad Natsir's political da'wah and his methods and strategies aimed at grounding and reintroducing the concept. Sources of data in this research consisted of primary and secondary sources of books/writings. This research data collection through documentation using content analysis techniques. The results of this research indicated that in political da'wah activities, Mohammad Natsir had the concept of modernization in Islamic p olitics. The essence of Natsir's concept of political modernism is to apply the teachings of Islamic spiritual, social and political values ​​contained in the Qur'an and Hadith, but still adapted and be opened to the period of times. Natsir carried out political da'wah with three methods, namely through the government field, the government field and the community development field. Natsir's political da'wah method was carried out using a da'wah strategy with actions, in writing, and orally. The implications of this research are expected to be the development of broader da'wah theories, especially those related to political da'wah in Indonesia.